نمذجة قياسية لمحـددات الطلب على الواردات الزراعية في الجزائر خلال الفترة 1990- 2020 - محلوس, زكية; بقاط, حنان (جامعة الوادي - University of Eloued, 2023)
We aim through this study to identify the most important variables that affect the demand for agricultural imports in Algeria. In this study, we used annual data for a time series during the period from 1990 to 2020. The Econometric study included checking the stability of time series by applying the developed Dickey-Fuller test and estimating a standard model using autoregressive models VAR with conducting the necessary statistical tests to diagnose the estimated model.. By analyzing the demand ray for agricultural imports, we concluded that there is a positive relationship between agricultural imports and their previous value, and an inverse relationship between the added value of the agricultural sector, slowed by one and two degrees of delay, and agricultural imports, and there is a direct relationship between agricultural imports and each of the total fixed capital formation slowed by one year. and two years, as well as a direct relationship with the exchange rate and the size of the population.
Econometric modeling of the Determinants of demand for agricultural imports in Algeria during the period 1990-2020
مقال
Keywords: المحددات ; الواردات الزراعية ; اختبار ديكي فولرالمطور ; نماذج الانحدار الذاتي ; الجزائر: Demand; Agricultural Imports; Developer Dickey-Fuller Test; Autoregressive Models; Algeria